Perceived Incivility and Stress of Final Year Nursing Students - Debora Purukan; Fristy Nemesis Mamengko; Putri Regina Sopamena; Ni Gusti Ayu Eka; Windy Sapta Handayani Zega (Universitas Muhammadiyah Yogyakarta, 2022)
Background: Incivility is disruptive behavior that can cause physiological or psychological distress to those involved. It can escalate into a potentially dangerous situation, such as serious suicidal tendencies and engaging in self-injury if left untreated. Incivility can be caused by various factors, one of which is stress. Objective: This study aims to examine the relationship between incivility and stress among final-year nursing students. Method: This study employed a quantitative research method using a correlation approach. It utilized simple random sampling. The data were analyzed using descriptive statistics and the Spearman rank test. The instruments included the INE-R/Incivility in Nursing Education-Revision (Cronbach Alpha 0.881-0.876) and the PSS/Perceived Stress Scale (Cronbach Alpha 0.684). This study recruited 200 students, the majority of whom were female (87.5%). Result: This study revealed students' perceived levels of incivility (Mean 20.93, SD 6.67); perceived frequency of incivility (Mean 18.01, SD 5.18); and perceived stress (Mean 22.01, SD 4.01). Additionally, this study discovered significant relationships between students' perceived levels of incivility and stress (p-value 0.010, r 0.283) and their perceived frequency of incivility and stress (p-value 0.001, r 0.269). Conclusion: Incivility has been associated with stress levels in nursing students. Nursing education must foster a positive learning environment. This study provided evidence for a correlation between incivility and stress in nursing students transitioning from blended to fully online learning due to the Covid-19 pandemic.